Voicing heartbreak: The sociopragmatics of ‘Cidra’ and Javanese masculinity in Didi Kempot’s lyrics - Iswatinginsih, Daroe; Tuan, Nguyen Thanh; Diana, Purwati Zisca; Rahmawati, Ida Yeni; Firmansyah, Ridho Covinda Wahyu (Universitas Ahmad Dahlan, 2025)
This study investigates the representation of cidra (heartbreak or betrayal of promise) and the construction of Javanese masculinity in Didi Kempot’s song lyrics through a sociopragmatic approach. Drawing on seven songs from four albums, the analysis proceeds in three steps: (1) segmenting the lyrics into expressive speech acts, (2) interpreting them through affective cultural scripts, and (3) situating the findings within masculinity discourses. The results reveal a tripartite model of male emotionality: (1) loyalty and patience that affirm Javanese cultural values, (2) emotional fragility expressed through crying and complaint, which challenges the script of stoic masculinity, and (3) resignation (lilo) as a culturally sanctioned coping mechanism. These dimensions converge into the concept of hybrid masculinity, which reconciles normative ideals with emotional expressions previously deemed inappropriate for Javanese men. Theoretically, this study contributes a sociopragmatic framework for analyzing emotional speech acts in non-Western contexts and positions popular music not only as a reflection but also as a site for reshaping gender norms. Practically, it demonstrates how Didi Kempot’s songs function as a form of collective cultural therapy, offering insights for culturally sensitive approaches to men’s mental health.